Dampak Pola Asuh Orang Tua Workaholic Terhadap Perkembangan Sosial Emosional Anak Usia Dini Usia 1-3 Tahun Di TPA Sekolah Laboratorium Paud Yasmin: Dampak Pola Asuh Orang Tua Workaholic Terhadap Perkembangan Sosial Emosional Anak Usia Dini Usia 1-3 Tahun Di TPA Sekolah Laboratorium Paud Yasmin - Oktavianti, Arindra; Purnamawati, Frimha; Arief Tukiman Hendrawijaya (Universitas Negeri Surabaya, 2025)
The problems faced by families today are not far from the busy work of parents. Workaholic is a term for working or workaholic parents. Because their busy lives result in parents lacking time to nurture, educate and guide children so that parents entrust children. This study aims to describe the impact of workaholic parenting on early childhood social-emotional development in Daycare Yasmin Laboratory School. The research method uses qualitative descriptively. The results showed that two parenting styles that occurred in the Daycare Yasmin Laboratory School were democratic parenting and authoritarian parenting. The impact of democratic parenting on social-emotional development is that children easily get along with their friends, have high self-confidence, have high curiosity, are able to work well together, are quick to respond, and have a polite attitude. While the impact of authoritarian parenting on social emotional development is that children are less able to appreciate, less able to get along with friends, and difficult to adjust in social situations.